Evaluating the causal association between bronchiectasis and different types of inflammatory bowel disease: a two-sample Mendelian randomization study - Zeng, Qian; Hu, Da; Li, Yuan; Zhou, Zhiwei; Wu, Jinfeng; Li, Xiaodong; Yu, Xiqiu (Frontiers in Immunology, 2024)
Background and Objectives: Previous observational studies have established a connection between bronchiectasis and inflammatory bowel disease (IBD), but none of these studies have provided a clear explanation for the underlying cause of this relationship. The present study thus implemented Mendelian randomization (MR) design to explore possible bidirectional relationships between IBD and bronchiectasis risk, with an additional focus on Crohn's disease (CD) and ulcerative colitis (UC) as IBD subtypes.A large genome-wide association study (GWAS)-derived data pool was leveraged to examine the relationships between bronchiectasis and IBD, CD, and UC. Twosample MR analyses were performed with an inverse variance weighted (IVW) approach supplemented with the MR-Egger and weighted median methods. Sensitivity analyses were used to further assess the reliability of the main MR study findings. The possibility of reverse causation was also evaluated using a reverse MR approach.The IVW MR analytical approach revealed that IBD (p = 0.074), UC (p = 0.094), and CD (p = 0.644) had no significant impact on the incidence of bronchiectasis, with the converse also being true (p = 0.471, p = 0.700, and p = 0.099, respectively).This MR-analysis demonstrated that the higher occurrence of bronchiectasis in patients with IBD is not caused by genetic predisposition.